Identification of a deletion containing TBX4 in a neonate with acinar dysplasia by rapid exome sequencing. Issue 5 (3rd March 2019) - German, Kendell; Deutsch, Gail H.; Freed, Amanda S.; Dipple, Katrina M.; Chabra, Shilpi; Bennett, James T.
Abstract : We describe a neonate with severe respiratory failure due to acinar dysplasia found by rapid exome sequencing (rES), to have a deletion containing the TBX4 gene. rES can affect patient management in the intensive care unit and should be considered in concert with lung biopsy in neonates with undifferentiated respiratory failure.